Comparison of HPCA Oil Tyre Tread Cap Compound with Low Polycyclic Aromatic Oil - Kumar, N.; Khandelwal, R.K.; Meena, P.L.; Meena, K.S. (Asian Journal of Chemistry, 2012)
Eco-friendly tires really live up to their name according to the independent tire retail giant, it depends on the tire. Most green tires claim to increase fuel mileage, helping to decrease a consumer's carbon footprint. As fuel economy regulations tighten and consumer demand for green transportation increases, tire manufacturers worldwide are adding precipitated silica to tread formulations to improve fuel efficiency, eliminate greenhouse gas emissions and enhance tire performance and handling. Reducing rolling resistance, or the amount of energy spent to move a vehicle, is an increasingly important solution to decreasing fuel consumption. In fact, tires are responsible for 20 to 30 % of a vehicle's fuel use. Rheology is principally concerned with extending the classical disciplines of elasticity and newtonian fluid mechanics to materials whose mechanical behaviour cannot be described with the classical theories. It is also concerned with establishing predictions for mechanical behaviour based on the micro- or nanostructure of the material, e.g. the molecular size and architecture of polymers in solution or the particle size distribution in a solid suspension. Materials flow when subjected to a stress that is a force per area. There are different sorts of stress (e.g. shear, torsional, etc.) and materials can respond in various ways. Thus much of theoretical rheology is concerned with the forces associated and external applied loads and stresses and the resulting internal strains. The object of this study was to investigate the MIN TQ. (lb-in), MAX TQ. (lb-in), Final TQ. (Ilb-in) of a tyre tread cap compound.